The North Korean Nuclear Dilemma: Does China Have Leverage?. (August 2019) - Zhang, Weiqi; Denton, Ginger L.
Abstract: North Korea has repeatedly defied the international community with regards to its nuclear weapons programme. Many look to China for leverage to change North Korea's behaviour. This study reviews the development of the China–North Korean relationship and conducts a statistical analysis on the impact of China's influence on North Korea. Our analysis finds China's leverage on North Korea to be nuanced. We maintain that North Korea has been wary of China's influence. Complete isolation or pressure from China under certain conditions will render North Korea more resistant to China's influence. We also suggest that the key to the North Korean issue is still in the hands of the United States and the entire international community through the use of an engagement strategy.